2016
DOI: 10.1016/j.ygyno.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Association between differential gene expression and body mass index among endometrial cancers from The Cancer Genome Atlas Project

Abstract: Objective The Cancer Genome Atlas (TCGA) identified four integrated clusters for endometrial cancer (EC): POLE, MSI, CNL and CNH. We evaluated differences in gene expression profiles of obese and non-obese women with EC and examined the association of body mass index (BMI) within the clusters identified in TCGA. Methods TCGA RNAseq data was used to identify genes related to increasing BMI among ECs. The POLE, MSI and CNL clusters were composed mostly of endometrioid EC. Patient BMI was compared between these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…Interrogating a total of 40,669 non-coding and 19,814 protein-coding genes in 302 obese and 213 non-obese TCGA-UCEC patients we identified four protein-coding genes and two non-coding genes with significant associations between expression and BMI. Two protein-coding genes identified are critical regulators of hormone-dependent tumour growth and also identified in the previous study [15]: growth regulating oestrogen receptor binding 1 ( GREB1 ) and progesterone receptor ( PGR ) were both positively associated (Spearman r =0.30, Q =5.71 × 10 -7 and r =0.30, Q =1.01 × 10 -6 , respectively) with body mass index (Table 2). A very recent study on an independent clinical data set revealed that PGR expression is indeed correlated with BMI in endometrial cancer [16, 17].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Interrogating a total of 40,669 non-coding and 19,814 protein-coding genes in 302 obese and 213 non-obese TCGA-UCEC patients we identified four protein-coding genes and two non-coding genes with significant associations between expression and BMI. Two protein-coding genes identified are critical regulators of hormone-dependent tumour growth and also identified in the previous study [15]: growth regulating oestrogen receptor binding 1 ( GREB1 ) and progesterone receptor ( PGR ) were both positively associated (Spearman r =0.30, Q =5.71 × 10 -7 and r =0.30, Q =1.01 × 10 -6 , respectively) with body mass index (Table 2). A very recent study on an independent clinical data set revealed that PGR expression is indeed correlated with BMI in endometrial cancer [16, 17].…”
Section: Resultssupporting
confidence: 58%
“…Indeed, such efforts are likely to reveal further BMI-associated cancer subtypes. Nevertheless, when distinct subtypes associated with overweight and obesity are evident, we and others [15] have shown that correlating gene expression and BMI alone across an entire data set is informative. We propose that an obesogenic environment is essential for the development of oesophageal adenocarcinoma (EAC), but not oesophageal squamous cell carcinoma (ESCC) – adding further weight to distinct prevention and treatment strategies for these histological subtypes [9].…”
Section: Discussionmentioning
confidence: 97%
“…Westin et al stratified cases by body mass index (BMI) revealed improved progression free survival in obese (BMI >30) women with endometrioid endometrial carcinoma suggesting an interaction between metabolic state and genetics [106]. Subsequently, a constellation of ‘obesity related’ genes are observed to be upregulated with increasing BMI among endometrioid carcinomas in the TCGA cohort [107], and different targets for treatment were suggested in obese vs non-obese individuals [108]. Given the global epidemic of obesity and associated ‘metabolic syndrome’, this clinical context is essential to know in guiding clinical management and in research/interpretation of data.…”
Section: Genotype-phenotype Interplaymentioning
confidence: 99%
“…Recently, gene expression profiling analysis has yielded insights into the measurement of alterations in genetic expression patterns, and has facilitated the identification of differentially expressed genes (DEGs) being crucial to obesity. In a study conducted by Roque DR, et al, obesity related genes, such as LPL, IRS-1, IGFBP4, and IGFBP7 , etc., were found to be upregulated with increasing BMI among endometrial cancer patients [ 12 ]. The study of Gruchala-Niedoszytko, M, et al also found a series of genes ( PI3, LOC100008589, RPS6KA3, LOC441763, IFIT1, and LOC100133565 ) with a different expression that may be related to an increased BMI [ 13 ].…”
Section: Introductionmentioning
confidence: 99%